Analisis Pengaruh Kebijakan Dividen, Dan Struktur Modal Terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Sektor Barang Konsumsi Yang Terdaftar Di Bei Periode 2019-2021) - Aisyah, Diana Sari; Rizal, Mohammad; Sholehuddin, Sulton (UNIVERSITAS ISLAM MALANG, 2024)
Abstract Finding out how capital structure and dividend policy affect a company's value is the main objective of this research. The research covers the years 2019–2021, and it focuses on consumer products businesses that are listed on the BEI in Indonesia. The Purposive Sampling method was used to select the sample. Multiple linear regression forms the basis of the procedure, which uses a t-test to assess hypotheses. The research concluded that capital structure (DER) and dividend policy (DPR) do not significantly affect company value. Keywords: Dividend Policy, Capital Structure and Company Value.